Compendium of Icebreakers, Volume 3 : Beginnings and Endings. - Barca, Michele (HRD Press, 2007)
The quizzes are organized in alphabetical order. They also are grouped in nine easy-access topic areas: Communication skills, customer service, health and safety, leadership, performance management, personal development, teamwork, recruitment and selection, and training and development. The quizzes are easy to administer in the classroom, too. Accompanying each quiz are suggested responses to the questions and helpful background information. You?ll find quizzes that ask participants to fill in the blanks, choose from several answers, rank items and pick between true and false. Action plans can.